2021
DOI: 10.21203/rs.3.rs-268142/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Perception of Jordanian Pharmacy Students towards Community Pharmacy-Virtual Training Experience during COVID-19 Outbreak

Abstract: Background: Nowadays, it is clear for the whole world that the coronavirus disease (COVID-19) pandemic had substantial consequences on various sectors including social, economic and education. Pharmacy education includes community pharmacy practice training, and in many schools, it has been shifted to virtual modality utilizing distance learning. This study aims to assess the perception of pharmacy students towards community pharmacy practice virtual training during the COVID-19 period. Methods: Senior pharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 22 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…In our study, 29% of students expressed the need for more interactive lectures, which they felt were lacking in OL. The impact of self-awareness and student engagement in online sessions on the success of OL was also recognized in previous studies [22,23].…”
Section: Discussionsupporting
confidence: 58%
“…In our study, 29% of students expressed the need for more interactive lectures, which they felt were lacking in OL. The impact of self-awareness and student engagement in online sessions on the success of OL was also recognized in previous studies [22,23].…”
Section: Discussionsupporting
confidence: 58%
“…At the faculty of pharmacy of Applied Science Private University in Jordan, senior fifth-year pharmacy students are offered a community pharmacy experience "Training II" course (Barakat et al, 2021).…”
Section: Many Universities Across the United States Closed Inmentioning
confidence: 99%
“…Discussion with students, which was led by the course instructor, was completed to achieve the course learning outcomes. The absence of eye contact during the training process was the most relevant barrier reported by students (Barakat et al, 2021). Recorded video tutorials were described as effective and supportive tools for pharmacy education (Farha et al, 2020).…”
Section: Sakr Et Al Experiential Pharmacy Education In Trying Timesmentioning
confidence: 99%
“…These include diverging (enjoy learning by watching and feeling), assimilating (enjoy learning by watching and thinking), converging (enjoy learning by doing and thinking), and accommodating (enjoy learning by doing and feeling) learning styles (Kolb, 1984). Studies reported that students positively perceived VPS-based training during the COVID-19 pandemic (De Ponti et al, 2020;Barakat et al, 2021). Understanding the different learning models can help design better individualised learning VPS.…”
Section: Impact Of Vps Use On Students' Satisfaction and Perceptionmentioning
confidence: 99%